Kehittäjäopettajien näkemyksiä ja kokemuksia Lupa Liikkua Lupa Harrastaa -toimintakulttuurista - Rosti, Krista (2024)
Recent studies have shown a decline in physical activity among children and adolescents. In primary school age, there are also a large number of pupils with no hobbies at all. The Finnish model for leisure activities has been designed to address these challenges by promoting free and voluntary low-threshold hobbies during the school day. This study examined the implementation of the Lupa liikkua Lupa harrastaa activity culture in Tampere, based on the Finnish model for leisure activities, from the perspective of the teachers who develop mobility and hobbies for children and young people. The aim of the LLLH activity culture is both to implement an active, mobile school day and to increase opportunities for hobbies in the school day. The purpose of this study was to explore the views and experiences of the development teachers on the implementation of the LLLH activity culture. This is a unique activity at national level, so no previous research data is yet available. This study has used previous studies on the Finnish model for leisure activities and on health promoting schools in several countries as a point of reference. The study was conducted as a qualitative case study, for which the research data was collected by interviewing seven development teachers in March-April 2023. The interview method was a semi-structured thematic interview.